Effect of Graphene Oxide Precursor Loading on the Surface of Melamine-Formaldehyde/rGO Sponge with Enhanced Ultra-Hydrophobicity for Oils Removal - Natcha Jirasuttisarn; Chaval Sriwong (My University, 2020)
This work presented a facile, green and effective method to prepare the ultra-hydrophobic melamine-formaldehyde (MF) sponge loaded with reduced graphene oxide (rGO) by a conventional heating method using the various contents of graphene oxide, GO (1, 3, 5, 10 and 15 mg) precursor, and vitamin C as a reducing agent. These GO precursors were used to increase the roughness of the MF/rGO sponge surfaces. Then GO precursor, rGO, pristine MF sponge and as-prepared MF/rGO sponge samples were confirmed and characterized by Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and water contact angle techniques. Moreover, the adsorption capacity, oils removal performance and recyclability of MF/rGO sponges were also investigated. The results showed that the water contact angle values were increased from 131 to 144.1 upon the increasing of GO precursor loading. The highest water contact angle (144.1) exhibited the ultra-hydrophobic property by the sponge prepared using GO loading as 10 mg (MF/rGO-10 mg). The adsorption capacity (Qe) of the MF/rGO-10 mg sponge was higher than 102 g.g-1 for all the oils removal tested (palm oil, gasoline, diesel and lubricant oil), and had the highest value was about 112 g.g-1 for lubricant oil. Besides, MF/rGO sponge can be well-recycled use up to 10 times for all oils removal. Therefore, this study provides a new alternative method to prepare the MF sponge loaded with rGO (MF/rGO), which can be used and reused for the cleanup of oil spillages from water.
Keywords: Sponge; Electrohydrodynamics and Fluid Dynamics